2020
DOI: 10.1016/j.bj.2020.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Neurocritical care of premature infants

Abstract: Neurocritical care is an approach of comprehensive care through multidisciplinary coordination and implementation of neuroprotective strategies to reduce the risk of neurologic injury among critically ill patients. Premature infants are at a special risk of sustaining brain injury and having adverse neurodevelopmental outcome. The pathogenesis of “encephalopathy of prematurity” is tightly linked to hemodynamic instability during postnatal transition, immaturity of the cerebral vascular bed and nervous system, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 70 publications
(72 reference statements)
0
13
0
4
Order By: Relevance
“…Reyin Lien summarises here all the parameters that require constant monitoring in order to avoid injuries to the brain, or at least minimise their impact, as well as the available techniques and therapies to fulfil the task [ 46 ].…”
Section: Also In This Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Reyin Lien summarises here all the parameters that require constant monitoring in order to avoid injuries to the brain, or at least minimise their impact, as well as the available techniques and therapies to fulfil the task [ 46 ].…”
Section: Also In This Issuementioning
confidence: 99%
“…Following on from the previous review by Lien et al. on the general picture of neurocritical care required in premature infants [ 46 ], Meng-Fai Kuo focuses here on intraventricular haemorrhage (IVH) and post-haemorrhagic hydrocephalus (PHH) in these patients [ 45 ].…”
Section: Also In This Issuementioning
confidence: 99%
“…The third part of this issue includes some challenging issues, such as abusive head trauma related to child abuse [ 7 ], anti-NMDA receptor encephalitis [ 8 ], neurocritical care and surgical management of intraventricular hemorrhage and posthemorrhagic hydrocephalus in premature infants [ 9 , 10 ]. In the third part, we also include two original articles of the studies of seizure outcomes after TTM and one study about the diminished Toll-like receptor response in FIRES [ [11] , [12] , [13] ].…”
mentioning
confidence: 99%
“…In the review article, it has been indicated that one of the future directions of neuroprotection in the premature infants is aiming at pharmacological prevention, specifically using agents with anti-inflammatory (e.g. melatonin) [ 1 ]. We think melatonin has many biologically possible behaviors that may effectively protect premature neonatal brains.…”
mentioning
confidence: 99%